(untitled) (University of Bucharest Review. Literary and Cultural Studies Series, 2024)
This article will explore American folk songs dealing with disasters, mostly from the first half of the twentieth century. These songs dealt with shipwrecks, train-wrecks, fires, tornadoes and drought and even the so-called Dust Bowl. Along with murder ballads, these songs functioned as a kind of oral newspaper providing information to even illiterate people in rural America. The songs also served as a stimulus to imagination, opening up exotic worlds to people often isolated and sedentary. The songs provided an opportunity for the listener/singer/musician to experience vicarious pain and catharsis in relation to the particular disaster. Finally, there was often a religious dimension to the songs and disasters which were being memorialised in song. The paper will conclude with a demonstration of how the disaster song finally became politicized with the example of Woody Guthrie. The primary source for the songs was the anthology of disaster songs entitled People Take Warning released in 2007. The artists included in the collection and discussed in this paper range from well-known figures such as the Carter Family and Charlie Poole to lesser known musicians who are practically forgotten. There will also be a discussion of the predecessors to these songs as well as the successors.